2018
DOI: 10.1016/j.tranon.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Treatments Increase PD-L1 Expression in Esophageal Squamous Cell Carcinoma through EGFR/ERK Activation

Abstract: The current study reveals the clinicopathological association of PD-L1 in Hong Kong esophageal squamous cell carcinoma (ESCC) patients and the differential regulation of PD-L1 by standard first-line chemotherapy in ESCC. Immunohistochemical analysis of tissue microarray data from 84 Hong Kong ESCC patients shows that PD-L1 was expressed in 21% of the tumors. Positive PD-L1 staining was significantly associated with later disease stage (stages III and IV) (P value = .0379) and lymph node metastasis (P value = .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 45 publications
3
53
0
Order By: Relevance
“…In particular, it has recently been shown that PD‐L1 significantly increased on residual disease after NACT compared with baseline in a large retrospective cohort of patients with TN early BC . The induction of PD‐L1 expression by chemotherapy is consistent with observations in other cancer types and with the notion that chemotherapy is able to induce an adaptive immune response through various mechanisms, including immunogenic cell death and the activation of the damage response c‐GAS/STING . Indeed, it has been shown that CT may boost the immunogenicity of the tumor by increasing tumor immune infiltrate from baseline to post‐NACT samples, with a high rate of conversion from low‐TIL to high‐TILs tumor .…”
Section: Methodssupporting
confidence: 71%
“…In particular, it has recently been shown that PD‐L1 significantly increased on residual disease after NACT compared with baseline in a large retrospective cohort of patients with TN early BC . The induction of PD‐L1 expression by chemotherapy is consistent with observations in other cancer types and with the notion that chemotherapy is able to induce an adaptive immune response through various mechanisms, including immunogenic cell death and the activation of the damage response c‐GAS/STING . Indeed, it has been shown that CT may boost the immunogenicity of the tumor by increasing tumor immune infiltrate from baseline to post‐NACT samples, with a high rate of conversion from low‐TIL to high‐TILs tumor .…”
Section: Methodssupporting
confidence: 71%
“…Moreover, at the end of a 2‐week treatment cycle, we observed that 4T1.2 and MDA‐MB‐231 tumors regained growth, suggesting the presence of a resistance mechanism against AF. In recent years, upregulation of immune checkpoint PD‐L1 has emerged as a potential resistance mechanism to neoadjuvant chemotherapies and targeted therapies . TNBC patients with high PD‐L1 expression on tumor cells have extremely unfavorable outcomes after chemotherapy compared to patients with low PD‐L1 expression .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, upregulation of immune checkpoint PD-L1 has emerged as a potential resistance mechanism to neoadjuvant chemotherapies and targeted therapies. 17,35 TNBC patients with high PD-L1 expression on tumor cells have extremely unfavorable outcomes after chemotherapy compared to patients with low PD-L1 expression. 40 Based on this data, it may imply that PD-L1 upregulation may lead to AF resistance in TNBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD‐L1 expression was assessed both in neoplastic epithelia and in infiltrating leukocytes. Three different parameters were considered: (a) PD‐L1 staining intensity in neoplastic cells categorizing cases in high (in presence of staining detected up to 5% of the neoplastic cells) and low (<5%) PD‐L1 expression; (b) a semiquantitative pathology H‐score, defined as the aggregate of total percentage of tumor cells expressing PD‐L1 at each particular intensity level from 0, +1 (weak intensity), +2 (moderate intensity) or +3 (strong intensity); in brief, the H score was defined as (Percent of PD‐L1 1+ tumor cells multiplied by intensity of 1) + (Percent of PD‐L1 2+ tumor cells multiplied by intensity of 2) + (Percent of PD‐L1 3+ tumor cells multiplied by intensity of 3), and this composite score can range from 0 (a tumor which is completely negative) to a maximum of 300 (a tumor in which all the cells feature a 3+ staining); (c) stromal positive leukocytes were counted in 5 HPF (40×) …”
Section: Methodsmentioning
confidence: 99%